2022-RA-787-ESGO ESGO guidelines on the management of endometrial cancer. Weaknesses and controversies in france and french-speaking switzerland. Results of a delphi survey. (20th October 2022) - Marti, Carolin; Deluche, Elise; Jochum, Floriane; Bendifallah, Sofiane; Azaïs, Henri; Deidier, Jonas; Cockenpot, Vincent; Menoux, Inès; Balaya, Vincent; Betrian, Sarah; Chargari, Cyrus; Gouy, Sebastien; et al.
Abstract : Introduction/Background: To assess the opinion of a panel of experts and obtain consensus on several issues from the ESGO recommendations on the management of endometrial cancer. Methodology: A Delphi survey was carried out among a panel of French and French-speaking Swiss experts. The questionnaire included 58 questions divided into 8 categories: characterization of experts, histo-molecular characteristics, radiological data, management of low-risk, intermediate-risk, intermediate-high-risk, high-risk and metastatic cancers. The experts were asked to reply on a 9-point scale, both on the validity and the clarity of each suggestion. After the answers were analysed, a second round was sent to the same experts for selected suggestions. To be accepted, each proposal had to obtain a median greater than or equal to 7/9. Results: The study was conducted between December 2021 and March 2022. 58 (57.4%) of 101 experts responded in the first round and 41 proposals were found. 5 questions were voted redundant and 19 discordant. These questions were reworded and partially split and at the end of the 2nd round, out of the 20 proposals 16 were validated and 4 rejected. In total, the study presents an analysis of 61 questions. Conclusion: These consensual recommendations are expected to standardize the management of endometrial cancer in France and French-speaking Switzerland and to optimize clinical practices.